Education using lecture methods and puppet media on knowledge and dental hygiene status in elementary school students - Julianti, Julianti; Rahayu, Culia; Rismayani, Lina (Center of Excellent (Pusat Unggulan Iptek), 2025)
Background: The high dental problems in elementary school children are caused by low knowledge and dental health behavior. Puppet media is effective to use because it provides real visualization that is interesting and easy for children to understand. This study aims to analyze the effect of education with the lecture method using puppet media on knowledge of dental health maintenance and dental and oral hygiene status in grade V students of SDN 1 Sindangkempeng, Cirebon Regency. Method: This research is a pre-experimental method with a one-group pretest-posttest design, with a total sample of 42 students. Results: based on the Wilcoxon statistical test with a p-value of 0.000, the results obtained were an increase in knowledge of dental and oral health maintenance of students to 86% with good criteria and an increase in the hygiene index to 74% of students having a good category. Conclusion: there is an effect of education with the lecture method using puppet media on knowledge of dental health maintenance and dental and oral hygiene status in elementary school students.